2023
DOI: 10.1007/s11356-023-25602-8
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal biochemical, behavioral, and physiological toxicity of extremely low dose of bendiocarb insecticide in Periplaneta americana (Blattodea: Blattidae)

Abstract: Insecticides are dedicated to impair the insect organisms, but also have an impact on other, non-target organisms, including humans. In this way, they became important risk factor for disturbance of physiological homeostasis and can be involved in the development of diseases or in deterioration of existing conditions. The influence of sublethal doses of various insecticides on vertebrates’ and invertebrates’ organisms has been previously observed. In this paper, we have evaluated the impact of exposure to extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…investigated the potential relationship between the glutathione antioxidant defense system in C. maculatus and the pesticidal effectiveness of several documented bio-insecticides and commercially synthetic insecticides. On contrary, Jankowska et al (2023) reported a considerable decrease in GSH concentration in the American cockroach, P. americana, after exposure to low dose (0.1 nM ) of carbamate insecticide, bendiocarb. This might be attributed to GSH's direct consumption as an antioxidant in the removal of ROS, which was heightened by the bendiocarb exposure.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…investigated the potential relationship between the glutathione antioxidant defense system in C. maculatus and the pesticidal effectiveness of several documented bio-insecticides and commercially synthetic insecticides. On contrary, Jankowska et al (2023) reported a considerable decrease in GSH concentration in the American cockroach, P. americana, after exposure to low dose (0.1 nM ) of carbamate insecticide, bendiocarb. This might be attributed to GSH's direct consumption as an antioxidant in the removal of ROS, which was heightened by the bendiocarb exposure.…”
Section: Discussionmentioning
confidence: 88%
“…At present, there is more attention has been considered on the effects of pesticides at sublethal dosages that don't directly affect insects, but induce some alterations in biochemical, behavioral, and physiological indices (Jankowska et al 2023). In insects, physiological systems may be altered as a result of exposure to sublethal pesticide dosages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As demonstrated in a prior investigation conducted by Singh et al (2022), the application of ZnO-NPs and ZnCl 2 has the potential to signi cantly increase the activity of SOD, CAT, and LPO, as well as the total GSH content, following a 28-day exposure period (p ≤ 0.05). The AChE enzyme, a neuro-biomarker, is a delicate enzyme that is present in the neural systems of both vertebrates and invertebrates and functions as an e cient neurological enzyme (Wong-Guerra et al, Jankowska et al, 2023). The study revealed that the highest dose of ZnO-NPs and ZnCl 2 resulted in elevated levels of the AChE enzyme.…”
Section: Discussionmentioning
confidence: 99%